Comparison of Conservative Management versus Drainage in Patients with Pancreatic Pseudocyst - Zeb, Mohammad Usman; Mahmood, Khalid; Malik, Muhammad Jalil; Anjum, Muhammad; Kaiser, Rabia; Bin Khalil, Huzaifa (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the conservative management of pancreatic pseudocyst with active surgical intervention.Study Design: Case series study.Place and Duration of Study: Department of General Surgery Combined Military Hospital, Rawalpindi Pakistan, from Jan 2020 to Apr 2021.Methodology: A total of 40 patients with pancreatic pseudocysts were included. The size of the pseudocysts, patients’ age,gender, lifestyle risk factors and possible aetiology were recorded. Conservative management was offered initially. The nonregressing and complicated pseudocysts were treated surgically via radiology-assisted external drainage or surgical drainage. Relevant data via close follow-up was recorded.Results: The mean age of the patients was 61±8.89 years. The pseudocyst size ranged from 4-17cm (median 10cm). Conservative treatment was efficacious in 15(37.5%) with shorter hospital stays (p-value